Tempo e espaço no currículo escolar - Brandão, Arlita Rodrigues (Universidade do Vale do Rio do Sinos, 2009)
To question the use of time-space in school curriculum in the formation of Modern subjects is the aim of this thesis. The empirical data was organized from the researcher insertion in a full-day school – CIEP, located in Santo Ângelo, Rio Grande do Sul. In order to analyze statements produced regarding full-day school-based, I assembled an analytic data of 22 photographic records justifying its choice. From the recurrence of statements it was defined the research question, as well as the three categories of analysis. The research question – “How time and space categories are implicated in curriculum practices concerned with the constitution of a desired school body inside certain social order in a full-day school?”. And, thereafter, the categories of analysis which allowed undergoing the interpretative paths: 1) time and space as elements for the constitution of the students in the curriculum practices; 2) curriculum practices as a collective involvement in school’s time-space; 3) pedagogical practices that r
Keywords: currículo; escola de tempo integral; subjetivação; tempo-espaço; curriculum; full-time schooling; subjetivation; time-space; Ciências Humanas